Moving beyond the concept of altered state of consciousness: the Non-Ordinary Mental Expressions (NOMEs) - Facco, Enrico; Fracas, Fabio; Tressoldi, Patrizio (Advances in Social Sciences Research Journal, 2021)
Aim of this paper is to review the state of the art of so-called altered states of consciousness, anomalous experiences, and exceptional human experiences, showing the need for reappraising the whole topic and gather them under one roof. The term Non-Ordinary Mental Expressions (NOMEs) and a new classification of non-pathological ostensibly odd phenomena is introduced, emphasizing their epistemological, transcultural and interdisciplinary implications with their huge implications in medical and psychotherapeutical clinical practice.